Effect of silane concentrations in hardener on the mechanical properties of jute/epoxy composites - Abdullah, Abdul Hakim; Azwa, Anis Zahrina; Tharazi, Izdihar; Adull Manan, Nor Fazli (UiTM Press, 2025)
Natural fibre-reinforced composites are sustainable and biodegradable materials that have potential in industry. However, hydrophilic natural fibres have issues with compatibility with hydrophobic matrix, causing poor mechanical properties. The application of silane coupling agents on fibre reinforcement has been well documented in the literature to enhance fibre/matrix interface properties in composites. In this paper, we investigated the effects of varying silane modifications of woven jute/epoxy composites in the hardener approach. The experimental works began with applying different concentrations of (3-aminopropyl) triethoxysilane (APTES); 1.5, 3.0, and 4.5 wt.% into the amine hardener. The composites were fabricated using the resin infusion technique. The panels were tested for moisture absorption, flexural properties and fracture toughness. The moisture absorption study reveals that the silane addition to jute/epoxy composites results in higher moisture content (3.51%-3.67%) after 5 days of immersion. The diffusion coefficient, D was calculated, and the value consistently decreases with increasing silane concentrations from the highest 2.65 x 10¯⁷mm² /s to the lowest 1.937 x 10¯⁷mm² /s. All silane-treated composites resulted in remarkable degradation in flexural strength and flexural modulus. The flexural strength and flexural modulus reduction were 16.3% - 39.2% and 4% - 15%, respectively. In contrast, the fracture toughness of composites increased significantly from 4.1 MPa√m to 6.2 MPa√m after 1.5 wt.% silane modifications in the hardener. It was found that increasing concentrations of silane do not necessarily enhance the fracture toughness of composites. Except for the improved fracture toughness, the obtained results indicated that the use of silane in the hardener approach has a negative effect on the moisture uptake resistance and flexural properties, which may be attributed to the ineffective fibre/matrix interfacial bonding.